Edukasi Warga Desa Sembahe Baru Dalam Rangka Peningkatan Penghasilan Melalui Ekonomi Kreatif Pengolahan Sampah Plastik - Wan Rizca Amelia; Ahmad Prayudi; Khairunnisak Khairunnisak; Ikbar pratama; Faras Cattleya Febrizaldy (Pelita Masyarakat, 2022)
A healthy environment is an important concern every year to show our quality of life. The accumulation of waste that becomes public concern really needs to be resolved with various parties, not only from the government, but also the involvement of the community as consumers of the plastic waste producer. This plastic waste damages ecosystems and habitats such as land, sea and air. So that this community service aims to educate the understanding of the dangers of plastic waste and increase the skills of the community regarding how to process plastic waste that has no value but can be processed into handicrafts that provide creative economic value. The results of beautiful handicrafts, of course, in the future can provide prospects for the community to help the economy so as to increase family income and can minimize damage to the environment, both land and air.